Pengembangan Wisata Warakas berbasis Edu Eco Wisata sebagai Penunjang Kampung Bahari Nusantara - Andhika Eko Prasetyo; Paramita Setyaningrum; Fandi Angga Prasetya (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The Government through the Creative Economy Program plans to build Kampung Bahari Nusantara (KBN) in Bungah sub-district. The implementation of this community service aims to provide assistance for the realization of KBN in Mengare. The implementation of the design of the Mengere area tourism development with the concept of Kampung Bahari Nusantara through several stages, namely extracting information about the potential that exists in the villages of Kramat, Tanjung Widoro, and Watu Agung using interviews and observations with snowball sampling techniques. The second stage is weighting the tourism potential that is easy to develop in each village. Next is a SWOT analysis (Strength, Weakness, Opportunity, and Threat). Based on the results of group discussions with the apparatus and several village leaders as well as the results of field observations, it was finally determined that Warakas Tourism in Tanjung Widoro Village was the first priority in the plan to develop a tourism cluster in the Mengere area. The results of the SWOT analysis show that access to the Warakas Tourism location in the Mengere area is very difficult to access. This requires a commitment from the Gresik Regency Government to widen the road and provide directions and street lighting. Based on market research, there are several facilities that need to be added in Warakas Tourism. With the additional 1.5 hectares of land that will be granted by Lantamal III, Warakas Tourism can be improved properly